2012
DOI: 10.1039/c2cp23886a
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl adsorption on solvated edge surfaces of pyrophyllite: a DFT model study

Abstract: In a computational study we addressed the adsorption of uranyl UO(2)(2+) on solvated (110) and (010) edge surfaces of pyrophyllite, applying a density functional approach to periodic slab models. We explored bidentate adsorption complexes on various partially deprotonated adsorption sites: octahedral Al(O,OH), tetrahedral Si(O,OH), and mixed AlO-SiO. Aluminol sites were determined to be most favorable on the (110) surface of pyrophyllite, while on the (010) surface mixed AlO-SiO sites are preferred. The struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 50 publications
10
38
0
Order By: Relevance
“…For example, static density functional theory (DFT) calculations of uranyl surface complexation on the basal and edge surfaces of kaolinite (Al 2 Si 2 O 5 (OH) 4 ) (Kremleva et al 2008(Kremleva et al , 2011Martorell et al 2010) revealed signifi cant differences between the tetrahedral Si layer and the octahedral Al layer, as well as a wide range of binding energies on different sites om the (010) edge surface. Similar conclusions were drawn from simulations of uranyl surface complexation on pyrophyllite (Al 2 Si 4 O 10 (OH) 2 ) edge surfaces (Kremleva et al 2012), where it was concluded that multiple adsorbed complexes likely exist on any given surface, and that different edge surfaces exhibit different preferred surface complex coordination environments.…”
Section: Molecular-scale Rates Of Uranyl Sorption Reactions At Minerasupporting
confidence: 57%
See 1 more Smart Citation
“…For example, static density functional theory (DFT) calculations of uranyl surface complexation on the basal and edge surfaces of kaolinite (Al 2 Si 2 O 5 (OH) 4 ) (Kremleva et al 2008(Kremleva et al , 2011Martorell et al 2010) revealed signifi cant differences between the tetrahedral Si layer and the octahedral Al layer, as well as a wide range of binding energies on different sites om the (010) edge surface. Similar conclusions were drawn from simulations of uranyl surface complexation on pyrophyllite (Al 2 Si 4 O 10 (OH) 2 ) edge surfaces (Kremleva et al 2012), where it was concluded that multiple adsorbed complexes likely exist on any given surface, and that different edge surfaces exhibit different preferred surface complex coordination environments.…”
Section: Molecular-scale Rates Of Uranyl Sorption Reactions At Minerasupporting
confidence: 57%
“…Mineral surfaces have included silica (Greathouse et al 2002;Patsahan and Holovko 2007;Boily and Rosso 2011), alumina (Moskaleva et al 2004;Glezakou and deJong 2011;Tan et al 2013), iron and titanium oxides (Steele et al 2002;Perron et al 2006aPerron et al ,b, 2008Drot et al 2007;Sherman et al 2008;Roques et al 2009;Skomurski et al 2011;Pan et al 2012;Sebbari et al 2012) , phyllosilicates (Zaidan et al 2003;Cygan 2005, 2006;Kremleva et al 2008Kremleva et al , 2011Kremleva et al , 2012Veilly et al 2008;Hattori et al 2009;Martorell et al 2010;Lectez et al 2012;Liu et al 2013b;Yang and Zaoui 2013a,b;Teich-McGoldrick et al 2014); feldspars Liu 2012, 2014), and carbonates (Doudou et al 2012). The majority of these studies focused on energy minimizations of adsorbed uranyl complexes at various mineral surfaces.…”
Section: Molecular-scale Rates Of Uranyl Sorption Reactions At Mineramentioning
confidence: 97%
“…In the monoclinic polytype, the symmetrically equivalent edges correspond to the (110) surface, and the unique edge is the (010) surface. In the triclinic polytype, the former edge coincides with the (010) surface, and the latter edge is approximately coincident with the (-110) surface (Bickmore et al, 2003;Kremleva et al, 2012;Newton and Sposito, 2015). In the current study, we use the original edge designations of White and Zelazny (1988).…”
Section: Introductionmentioning
confidence: 92%
“…These theoretical results were in good agreement with the EXAFS data. Recently, the adsorption of UO 2 2+ on the 2:1 clay mineral pyrophyllite have been examined by density functional approach and the structural parameters of the adsorption complexes on the (110) and (010) surfaces agreed very well with available EXAFS data for uranyl adsorption on mineral montmorillonite …”
Section: Actinide Computational Chemistry Associated With Exafs and Xmentioning
confidence: 99%